PENGARUH PENGGUNA TEKNOLOGI INFORMASI, DISIPLIN KERJA, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA GURU DI SMA MUHAMMADIYAH 1 PONOROGO - Viona Rosalina Malindasari; Naning Kristiyana; Wahna Widhianingrum (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
Human resources have a role that can determine the success of all activities in the school. Therefore, the performance of teachers in a school will depend on how the human resources are managed. Teachers are the spearhead in efforts to improve the quality of services and educational outcomes. Therefore, the school seeks to prepare human resources to face the times. Information technology (IT) has increased very rapidly in the current era, as can be seen from the use of technological equipment whose sophistication continues to increase with increasing reach. In the world of education, the application of information technology is needed to support the operational activities of educational institutions such as schools. Work discipline has an important role in achieving national education goals, because with high work discipline teachers can complete work and carry out appropriate learning according to predetermined standards so that high performance of a teacher will be achieved. Including the physical work environment in an organization has an important meaning for individuals who work in it, because the environment will affect individual satisfaction at work. This research is a type of quantitative descriptive research because in the process it uses numerical processing to be calculated through statistical tests. The sample in this study was 45 teachers at SMA Muhammadiyah 1 Ponorogo. Data collection techniques using research instruments, namely questionnaires. The analytical tool used is multiple linear regression. The results of this study are the ability to use information technology, work discipline, and physical work environment, have a positive effect on teacher performance at SMA Muhammadiyah 1 Ponorogo